Advisory services boost bean farming in Malawi - Chideya, Yohane; Magwaya, Eunice; Nkhata, Wilson; Rubyogo, Jean Claude; Moyo, Nobel; Madzonga, Oswin (2025)
The Southern Africa Accelerated Innovation Delivery Initiative (AID-I) has made a significant impact on smallholder bean farming in Malawi, especially during the challenging 2023-24 cropping season, exacerbated by an El Niño-induced drought. Through innovative advisory services, AID-I facilitated the adoption of climate-smart practices, including drought-tolerant seeds and improved soil management techniques. The initiative has empowered farmers like Monica Levison and Liden Mbengo to overcome challenges and increase their yields. By focusing on seed multiplication, effective agronomic practices, and extensive training, AID-I has enhanced food production and resilience among smallholders. The project has trained over 11,000 farmers, with a notable percentage of women, driving community-level agricultural transformation. These efforts have not only improved crop yields but also sparked long-term economic growth, food security, and resilience in Malawi’s farming communities.